Simultaneous estimation of temperature and emissivity of metals around their melting points by deterministic and Bayesian techniques. (February 2022) - Pierre, Thomas; Krapez, Jean-Claude; Orlande, Helcio R.B.; Rodiet, Christophe; Maux, Dylan Le; Courtois, Mickaël; Masson, Philippe Le; Lamien, Bernard
Highlights: The temperature and the emissivity of niobium and steel are estimated around their melting points by multispectral pyrometry. The experimental data are radiative fluxes collected by a six-wavelength pyrometer and by a commercial bichromatic pyrometer. The apparatus is dedicated to the characterization of the physical properties of millimeter-size metal samples at high temperatures, combining aerodynamic levitation and laser heating. Different techniques are used are based on deterministic (ordinary least squares) and Bayesian approaches. Abstract: This article presents the temperature and emissivity estimation of metals around their melting points using different techniques, which are based on deterministic (ordinary least squares) and Bayesian approaches. Linear and non-linear models are examined. The experimental data consist of radiative fluxes at six wavelengths, collected by a pyrometer. The apparatus is dedicated to the characterization of the physical properties of millimeter-sized metal samples at high temperatures, combining aerodynamic levitation and laser heating. Tests are performed on two metals: niobium with well-known temperature and steel.